2001
DOI: 10.2337/diabetes.50.6.1505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Novel Polymorphisms in the RAGE Gene on Transcriptional Regulation and Their Association With Diabetic Retinopathy

Abstract: Interactions between advanced glycation end products (AGEs) and the receptor for AGE (RAGE) are implicated in the vascular complications in diabetes. We have identified eight novel polymorphisms, of which the ؊1420 (GGT)n, ؊1393 G/T, ؊1390 G/T, and ؊1202 G/A were in the overlapping PBX2 3 untranslated region (UTR), and the ؊429 T/C (66.5% TT, 33.5% TC/CC), ؊407 to -345 deletion (99% I, 1% I/D, 0% D), ؊374 T/A (66.4% TT, 33.6% TA/AA), and ؉20 T/A were in the RAGE promoter. To evaluate the effects on transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
206
5
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(226 citation statements)
references
References 22 publications
10
206
5
1
Order By: Relevance
“…Given the presence of LD between these polymorphisms as has been reported in other studies as well, 18,19 we also performed haplotype tests for association which also yielded no evidence for association. In this study, we also compared the allele frequencies between the nondiabetics and the DM group, and also found them to be similar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the presence of LD between these polymorphisms as has been reported in other studies as well, 18,19 we also performed haplotype tests for association which also yielded no evidence for association. In this study, we also compared the allele frequencies between the nondiabetics and the DM group, and also found them to be similar.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-RFLP genotyping was carried out as described. 18 PCR consisted of 100-150 ng of DNA denaturing at 941C, annealing at 561C, extension at 721C for 30 cycles, followed by a final extension at 721C for 5 min in a 50 ml reaction. The PCR products were then digested with Alu I (New England Bio Labs) at 371C for 6 h for À429 T/C polymorphism and Tsp509 I (New England Bio Labs) at 651C for 16 h for À374 T/A polymorphism.…”
Section: Pcr-rflpmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, recently identified polymorphisms within the promoter of the gene encoding RAGE may hold the key to unique elements controlling enhanced transcription of the RAGE gene and increased expression of cell surface RAGE. 54 As a number of studies have suggested that expression of RAGE is increased at sites of ligand accumulation such as diabetic atherosclerotic lesions, infected periodontium or Alzheimer disease brain, 13,18,55 polymorphisms within regulation elements and/or ligand-binding regions may, alone or in combination, orchestrate RAGE's availability and/or functional potential in a given milieu. 56 In conclusion, we propose that these observations in an animal model of inflammatory arthritis and in S100/calgranulin-stimulated activation of 82S RAGEbearing cells highlight ligand-RAGE engagement as an amplifier of proinflammatory mechanisms in immune/ inflammatory diseases.…”
Section: Rage 82s Allele and Association With Rheumatoid Arthritismentioning
confidence: 99%